Hypoglycemia impact on psychiatric symptoms and brain changes in anorexia nervosa - Przemysław Zaroda; Paweł Dąda; Paweł Pawlik; Patrycja Niewinna; Michał Żuchowski; Dominika Mańdziuk; Klaudia Kołodziej; Wojciech Kołodziej; Jakub Wawrzkowicz; Monika Korga (Kazimierz Wielki University, 2024)
This study examines the potential impact of hypoglycemia on mental comorbidity in anorexia, comparing it to similar changes in diabetes. Anorexia, characterized by low body weight, is linked to hypoglycemia, possibly affecting mental health. Recurrent hypoglycemia in diabetes leads to mood changes and cognitive impairment. Anorexic individuals may experience deficits in cognitive functioning and psychiatric comorbidities, including affective disorders and anxiety. Imaging studies show structural changes in the brains of both anorexia and diabetes patients, but the direct link between hypoglycemia and psychoorganic changes in anorexia remains inconclusive, warranting further investigation.